Supply and Consumption Trends in Egyptian Fish Markets, 2000 to 2017 - Murphy, Seamus (2018)
As part of the IFPRI Egypt Seminar in partnership with WorldFish: “Leveraging Aquaculture and Fisheries for Improving Food and Nutrition Security in Egypt”